2013
DOI: 10.1590/s0100-204x2013000800004
|View full text |Cite
|
Sign up to set email alerts
|

Coliform density in oyster culture waters and its relationship with environmental factors

Abstract: -The objective of this work was to evaluate the total and thermotolerant coliform densities in the oyster culture water of Cananeia, SP, Brazil, correlating these densities with environmental variables and tidal variations. Superficial water samples were collected in two tide conditions (spring and neap) from three areas of Cananéia municipality (Mandira, Itapitangui and Cooperostra). The three studied areas showed good conditions for the culture regarding coliform densities. The two tidal conditions differed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
2
16
0
5
Order By: Relevance
“…Results of this study are consistent with other research projects. The inverse relationship between salinity and fecal coliform bacteria in water has been demonstrated in laboratory tests (Šolić & Krstulović, 1992) and in coastal marine environments (Barrera-Escorcia & Namihira-Santillán, 2004;Mignani et al 2013). Anacleto et al (2013) indicated that E. coli concentrations in seawater and sediments of the Targus Estuary (Portugal) were significantly higher during the rainy season.…”
Section: Vega Corrales and Marín Vindasmentioning
confidence: 87%
See 1 more Smart Citation
“…Results of this study are consistent with other research projects. The inverse relationship between salinity and fecal coliform bacteria in water has been demonstrated in laboratory tests (Šolić & Krstulović, 1992) and in coastal marine environments (Barrera-Escorcia & Namihira-Santillán, 2004;Mignani et al 2013). Anacleto et al (2013) indicated that E. coli concentrations in seawater and sediments of the Targus Estuary (Portugal) were significantly higher during the rainy season.…”
Section: Vega Corrales and Marín Vindasmentioning
confidence: 87%
“…Recent studies have shown that concentrations of E. coli in bivalve mollusc growing areas depend on, among many other factors, seasonal and climatic conditions of the area (Campos et al 2013b;Derolez et al 2013;Lee & Silk, 2013;Mignani et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the expansion of oyster farming in the tropical regions is linked to domestication and the development of technological basis for native species. The bottom oyster C. gasar stands out among the potential native species for oyster culture, since it reaches larger sizes than C. rhizophorae (CHRISTO and ABSHER, 2006), and it has been farmed with relative success in the states of Paraná (BALDAN and BENDHACK, 2009) and São Paulo (MIGNANI et al, 2013;COLLAÇO et al, 2014;DOI et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(Dollfus and Dautzenberg 1920). Oysters cultivation in the Estuarine-Lagoon Complex of Cananeia-Iguape (ELCCI) has an important economic significance for local fishing communities (Henriques et al, 2010;Mignani et al, 2013;Machado et al, 2015;Doi et al, 2015). Since 1997, oyster farming has occurred artificially, in suspended or tray systems.…”
Section: Introductionmentioning
confidence: 99%